2000
DOI: 10.1093/geronb/55.4.s234
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Care for Dementia Sufferers in Long-Term Care Institutions: Are They Related to Outcomes?

Abstract: Objectives. This study empirically examined whether dimensions of care cluster in special care units (SCUs) compared with non-SCUs. The relationship between SCU status plus separate measures of the dimensions of care and outcomes for dementia sufferers was then investigated.Methods. Data were drawn from the Intermediate Care Facility Project. The sample ( N ϭ 510) included residents with dementia, aged 65 and older, in intermediate care facilities throughout the province of British Columbia, Canada. Longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
2
37
0
4
Order By: Relevance
“…D'autres auteurs ont aussi discuté ces propositions la même année [33,34]. L'implication de la famille s'est ensuite ajoutée à la définition et se trouve souvent évoquée [35][36][37]. Mais les structures qui se définissent comme SCU ne proposent pas toutes les mêmes critères.…”
Section: Caractéristiques Des Unités De Soins Spécialisées Alzheimer unclassified
“…D'autres auteurs ont aussi discuté ces propositions la même année [33,34]. L'implication de la famille s'est ensuite ajoutée à la définition et se trouve souvent évoquée [35][36][37]. Mais les structures qui se définissent comme SCU ne proposent pas toutes les mêmes critères.…”
Section: Caractéristiques Des Unités De Soins Spécialisées Alzheimer unclassified
“…Although the literature that came out of the National Institute on Aging Collaborative Studies of Dementia Special Care Units and the work of the various members of The Gerontological Society of America's Workgroup on Research in Special Care Units focused on nursing homes , much of that work is relevant to dementia services in assisted living. Overall, although providers and experts generally believe that SCUs offer benefits to residents, most of the research on SCUs in nursing homes has found that living in an SCU does not, in itself, appear to lead to better outcomes (Chappell & Reid, 2000;Phillips et al, 1997). For example, a study of the advantages of mainstreaming versus living in a special unit in assisted living (Kuhn, Kasayka, & Lechner, 2002) suggested that mainstreamed residents might be more engaged in social activities.…”
Section: Characteristics Of Rc/al Settings Serving People With Dementiamentioning
confidence: 99%
“…In the long-term-care field, most research has focused on the relationship of structure and process, as mediated by resident characteristics, on resident outcomes. Chappell and Reid (2000) identified five dimensions of care in their literature review that are generally considered to be relevant to outcomes in dementia care. These are: assessment and diagnosis; staff specialization and ongoing education; nonuse of restraints (both physical and chemical); flexible care routines, including client-relevant activities; and specialized environmental design and adaptation.…”
Section: Regulatory and Third-party Payer Issuesmentioning
confidence: 99%
“…Analyses of the connection between the dimensions of care and patient-related outcome variables indicate that for a large sample of dementia patients (510 residents in long-term care institutions in Canada) there is a significant, though not particularly marked, correlation between staff training and the patients' agitation [62]. The more training the staff received, the smaller the rise in agitation in the course of a year.…”
Section: Staff Trainingmentioning
confidence: 99%
“…No significant correlation was established between staff training and the patients' physical functioning, expressive language skills, social skills, affect or cognitive functioning. The scores given by Chappell and Reid [62] to the value of staff training relate to a large variety of different types of training conducted in the care units which were studied, but the question remains as to which kinds of staff training most effectively influence the behaviour of the dementia patients, and this question can be answered only by using results from intervention studies.…”
Section: Staff Trainingmentioning
confidence: 99%